A review of spectral controlling for renewable energy harvesting and conserving. (May 2021) - Wu, Zuoxu; Wang, Jian; Liu, Yijie; Hou, Shuaihang; Liu, Xingjun; Zhang, Qian; Cao, Feng
Abstract: Exploiting renewable energy is an extremely effective strategy for alleviating and addressing the energy issues. To effectively harvest renewable energy, the investigations of fundamental thermodynamics resources of the sun and outer space have attracted significant attentions and various attempts have been carried out for energy-related applications. The key of effective energy harvesting and conserving from the sun and outer space relies on the precise manipulation of the electromagnetic responses including selective reflection, transmission, and absorption/emission in particular frequency ranges, which plays a critical role in various practical applications. According to the utilization of spectral bands, the electromagnetic responses are summarized into the single-band and multi-band characteristics. The single-band applications including the photovoltaic and photothermal conversion, thermal photons radiation, radiation cooling, and smart windows coatings, enable individually the utilization of the solar energy or the thermal radiation. In addition, the hybrid photovoltaic-thermal system and solar absorber/thermal emitter subtly synergize the photovoltaic and photothermal or thermal radiation through multi-band spectral modulation. In order to figure out the basic mechanisms of existing renewable energy technologies based on various electromagnetic responses, herein, we briefly summarize the optical characteristics from the perspective of spectral tuning and review their corresponding practical technologies. This article aims to provide a perspicuous mainline for existing spectral controlling work and to inspire other innovative optical tuning for potential energy applications. Graphical abstract: Image 1 Highlights: Spectral controlling mechanism and strategy involving the optical materials and engineered optical structures are reviewed. The optical responses are summarized into single- and multi-band characteristics based on the utilization of spectral bands. The challenges and perspectives are discussed about the specific applications of renewable energy harvesting and saving.